Improved understanding of drought controls on seasonal variation in Mediterranean forest canopy CO2 and water fluxes through combined in situ measurements and ecosystem modelling - Keenan, T; Garcia, R; Friend, A D; Zaehle, S; Gracia, C; Sabate, S (BIOGEOSCIENCES, 2009)
Water stress is a defining characteristic of Mediterranean ecosystems, and is likely to become more severe in the coming decades. Simulation models are key tools for making predictions, but our current understanding of how soil moisture controls ecosystem functioning is not sufficient to adequately constrain parameterisations. Canopy-scale flux data from four forest ecosystems with Mediterranean-type climates were used in order to analyse the physiological controls on carbon and water flues through the year. Significant non-stomatal limitations on photosynthesis were detected, along with lesser changes in the conductance-assimilation relationship. New model parameterisations were derived and implemented in two contrasting modelling approaches. The effectiveness of two models, one a dynamic global vegetation model ({''}ORCHIDEE{''}), and the other a forest growth model particularly developed for Mediterranean simulations ({''}GOTILWA+{''}), was assessed and modelled canopy responses to seasonal changes in soil moisture were analysed in comparison with in situ flux measurements. In contrast to commonly held assumptions, we find that changing the ratio of conductance to assimilation under natural, seasonally-developing, soil moisture stress is not sufficient to reproduce forest canopy CO2 and water fluxes. However, accurate predictions of both CO2 and water fluxes under all soil moisture levels encountered in the field are obtained if photosynthetic capacity is assumed to vary with soil moisture. This new parameterisation has important consequences for simulated responses of carbon and water fluxes to seasonal soil moisture stress, and should greatly improve our ability to anticipate future impacts of climate changes on the functioning of ecosystems in Mediterranean-type climates.
APS
Keywords: ecosystem functioning; forest ecosystems; Mediterranean; water stress

¿Puede la gestión forestal mitigar los efectos de un incremento de sequía en los montes mediterráneos? El caso de los bosques de encina y roble en el contexto del cambio climático. - COTILLAS, M; ESPELTA, J M; Sabate, S (V Congreso Forestal Español, 2009)
Uno de los grandes retos para la conservación de los ecosistemas forestales a lo largo del presente siglo es el cambio climático, del que se esperan importantes repercusiones en la cuenca mediterránea. Los modelos climáticos proyectan para esta área un descenso en la precipitación que, unido a un aumento de las temperaturas, acrecentará la ya de por sí característica sequía estacional que caracteriza esta zona. Dadas estas proyecciones, se hace necesario determinar los efectos que tendría una reducción de la precipitación en las diferentes especies que componen nuestros bosques, para poder así estimar posibles cambios en la estructura y composición de los mismos e identificar estrategias de gestión adecuadas para mitigar su efecto. En este contexto, el objetivo de nuestro estudio es analizar los efectos de una reducción de la precipitación en el monte bajo de encina (Quercus ilex L.) y roble (Quercus cerrioides Willk & Costa), así como evaluar los efectos de la gestión (resalveo) en su respuesta a este. Para ello, se combinan en un bosque mixto dos niveles de precipitación (precipitación natural vs. reducción de la precipitación de un 15%) y gestión (no gestión vs. gestión) en cuatro tratamientos. Se analiza la mortalidad, crecimiento, nueva rebrotada y dinámica foliar. Tras cuatro años de seguimiento el experimento sigue en curso, y hasta ahora se han obtenido los resultados definitivos de mortalidad, crecimiento y nueva rebrotada, que muestran que: i) La gestión reduce fuertemente la mortalidad, ii) El crecimiento de los robles se ve notablemente afectado por la reducción de precipitación, mientras que el de las encinas permanece constante, iii) La gestión incrementa fuertemente el crecimiento en ambas especies, especialmente en condiciones de precipitación natural. Actualmente se están comenzando a analizar los datos de dinámica foliar, y los resultados preliminares muestran que iv) Las parcelas sometidas a reducción de precipitación presentan un número menor de hojas, una menor longevidad de las mismas, y una mayor tasa de caída de hojarasca que las no sometidas a este tratamiento, v) La gestión atenúa la caída de hojas en todas las parcelas, mitigando los efectos de la reducción de precipitación en las parcelas sometidas a este tratamiento. De estos resultados se extrae la conclusión de que el cambio climático puede tener consecuencias negativas sobre los bosques de Quercus mediterráneos, siendo más acusados los efectos en robles caducifolios. Sin embargo, la gestión forestal puede ser una potente herramienta para mitigar estos efectos y conservar nuestros bosques de cara al futuro.
Keywords: cambio climático; Quercus cerrioides; Quercus ilex; resalveo; sequía

Thinning effects on carbon allocation to fine roots in a Quercus ilex forest - López, B C; Sabate, S; Gracia, C A (Tree Physiology, 2003)
The dynamics of the fine root system are relevant to calculations of the carbon balance of the ecosystem, and there is also a need to quantify changes in this component caused by disturbances. Mediterranean forest systems have historically been coppiced to obtain charcoal. As a result of the resprouting capacity of holm oaks (Quercus ilex L.), these forests present more than 50% of their biomass below ground (stump + roots > 1 cm in diameter), but the effects of thinning on the fine root system are unknown. Fine root biomass, production, mortality and longevity were studied in a control and a thinned Mediterranean holm oak forest by minirhizotron methodology. Observations of fine roots started 2 years after thinning and continued for almost 3 years. Extraction of 80% of the former basal area of the forest greatly affected carbon allocation patterns. Biomass increased by more than 100%, production increased by 76%, mortality increased by 32% and longevity decreased by around 2 weeks. The greatest differences between treatments were associated with differences in growth during autumn months in the top 40 cm of soil, particularly between 10 and 20 cm depth.
10.1093/treephys/23.17.1217
Keywords: biomass; longevity; mortality; production

Fine-root longevity of Quercus ilex - López, B; Sabate, S; Gracia, C A (New Phytologist, 2001)
* • Fine-root longevity and phenology were studied in a Quercus ilex (holm oak) forest in Prades (NE Spain). Differences were investigated among roots that had appeared in different seasons and at different depth intervals, differentiating between white and brown roots. * • Using minirhizotrons installed in March 1994, 1211 roots were monitored every 3 wk from June 1994 to March 1997. * • Mean and median fine-root longevity were 125 ± 4 d and 67 d, respectively. Longevity of summer and winter roots was greater than that of spring and autumn roots. Although roots appeared and disappeared throughout the year, the rate of appearance was greatest in spring. Maximum longevity occurred at a soil depth of 20–30 cm. Differences among 10-cm depth intervals were due to the number of days that roots were brown, since roots remained white for a similar number of days, independent of soil depth. * • Temperate soil temperatures and lignotubers permitted the appearance of roots throughout the year. Holm oak fine roots might be more efficient during the first 50 d of their life before the white roots become less efficient brown roots.
Keywords: Fine root longevity; Holm oak; minirhizotron; Quercus ilex; vertical longevity pattern

Effects of elevated CO2 and decreased water availability on holm-oak seedlings in controlled environment chambers - López, B; Sabate, S; Ruiz, I; Gracia, C (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
In Mediterranean ecosystems, water is an important limiting factor for plant growth. In addition to the increase in atmospheric CO2, some models predict increased drought in Mediterranean areas as a consequence of global change. Thus, to determine how increased atmospheric CO2 interacts with increased water stress and affects Mediterranean plant growth is an important achievement. The present study analyses how helm oak (Quercus ilex L.) seedlings are affected by both elevated CO2 and increased water stress. The CO2 concentrations were supplied in controlled environment chambers (350 and 500 ppm CO2), and water stress was performed according to a Mediterranean pattern (Potential Evapotranspiration to Rainfall ratio). The increased water stress was attained by watering half of the Mediterranean reference pattern. Results show that the positive effects of elevated CO2 on photosynthesis and growth are counteracted by increased water stress.
Keywords: CO2; controlled environment chambers; Quercus ilex

Modelling the responses to climate change of a Mediterranean forest managed at different thinning intensities: Effects on growth and water fluxes - Gracia, C A; Sabate, S; Tello, E (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
This study explores the effect of various climatic change scenarios over a 50 year period on plots managed at a range of thinning intensities. In order to determine how management practises can modify the effect of climatic change on Mediterranean Forests we integrated field experiments and the results of the GOTILWA model so as to take into account both water fluxes and forest structure interactions. The results show that the positive effects of atmospheric CO2 fertilisation, causing an increase in WUE, counteract with the negative effects of both temperature increase and rainfall decrease. Thinning might attenuate the effects of adverse conditions by reducing both leaf respiratory costs and the foliage turnover rate.
Keywords: climate change; mediterranean forest; Modelling

Nutrient content in Quercus ilex canopies: seasonal and spatial variation within a catchment - Sabate, S; Sala, Anna; Gracia, C A (Plant and Soil, 1995)
Spatial and temporal changes in canopy nutrient content were studied in 1988 and 1989 in a Mediterranean Quercus ilex ssp. ilex L. forest in north-eastern Spain. Sampling was conducted in parallel at two sites which represent endpoints along a slope gradient within a small catchment (ridge top at 975 m and valley bottom at 700 m). Deeper soils resulted in significantly higher N and P concentrations, and N content on a leaf area basis at the valley bottom site. In contrast, K concentration in leaves was significantly higher at the ridge top site, where soil K concentration was also higher. At both sites, N and P content on a leaf area basis was highest at the top of the canopy, where leaf area is highest. N resorption efficiency decreased from top to bottom of the canopy. Results suggested a minor role of shaded leaves as nutrient storage sites. Lower P resorption efficiency was found at the ridge top site. Seasonal changes of P and N concentration on a leaf area basis suggest P replenishment, and to a lesser degree N, during periods of lower growth activity due to low temperatures, but coinciding with higher water availability (autumn-early spring period). Thus, N and P resorption from the remaining foliage in the canopy took place, and to a larger degree at the valley bottom site, coinciding with a slightly higher leaf area index and productivity at this site.
Keywords: Canopy; nutrient content and dynamics; nutrient resorption; Quercus ilex

Canopy structure within a Quercus ilex forested watershed: variations due to location, phenological development, and water availability - Sala, A; Sabate, S; Gracia, Carlos; Tenhunen, J D (Trees-Structure and Function, 1994)
Spatial and temporal changes in canopy structure were studied in 1988 and 1989 in a Mediterranean Q u e r c u s ilex forest in north-eastern Spain. Due to differences in precipitation patterns the 1989 growing season was drier than the 1988 growing season. Sampling was conducted in parallel at two sites which represent endpoints along a slope gradient within a watershed (ridge top at 975 m, and valley bottom at 700 m). At both sites, similar inter-annual changes in canopy structure were observed in response to differences in water availability. Samples harvested in the upper 50 cm of the canopy during 1989 exhibited a de- crease in both average leaf size and the ratio of young to old leaf and stem biomass relative to samples obtained in 1988. At the whole canopy level, a decrease in leaf pro- duction efficiency and an increase in the stem to leaf bio- mass ratio was observed in 1989. Temporal changes in canopy leaf area index (LAI) were not statistically sig- nificant. Average LAI values of Q. ilex at the two sites were not significantly different despite differences in tree stature and density (4.6 m 2 m -2 at the ridge top, and 5.3 m 2 m -2 at the valley bottom). Vertical distribution of leaves and stems within the canopy was very similar at the two locations, with more than 60% of the total LAI in the uppermost metre of the canopy. The possible significance of such an LAI distribution on the canopy carbon budget is discussed.
Keywords: Canopy structure; leaf area index; Mediterranean sclerophylls; Quercus ilex; water deficit

ASPECTOS ECOFISIOLOGICOS RELACIONADOS CON LA PRODUCCION DE LOS ENCINARES MEDITERRANEOS - Gracia, C A; Sala, A; Sabate, S (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The productivity of Quercus ilex forests is low in relation to other tree species. Waterand nutrients are often the most important limiting factors. Nevertheless the ecophysiological traits of this specie could help to explain the observed patterns of productivity. Leaf area index of european evergreen-oak forests is rather constant with values about 5. The energetic cost of formation and maintenance of the leaves of Quercus ilex accounts for more than 50 per cent of total carbon fixed by the trees. The resproutig ability of evergreen oaks could explain the high density and low mean diameter of these populations. The high proportion of living tissues in this type of structuni increases the respiration costs of the stems and branches. As a consequence, an important fraction of carhon fixed by leaves is used to maintain the structure of the community which contribute to explain the low observed net primary production of Quercus ilex forests
Keywords: ecophysiology; L.A.I.; productivity; Quercus ilex

Preliminary results of a fertilization-irrigation experiment in a Quercus ilex L. forest in relation to leaves and twigs characteristics - Sabate, S; Calvet, S; Gracia, C A (Plant Ecology, 1992)
A multifactorial ANOVA experiment was designed for a Quercus ilex forest in the Prades mountains in Tarragona (NE Spain). The purpose of this study was to clarify the relative importance of water, ni- trogen and phosphorus as factors controlling primary production. Eight plots comprising all possible combinations of the three factors (including a control) were laid out in three replicate blocks. Fertilizers were applied to the appropriate treatments in March 1989 with a dosage of 125 kg of P/ha and 250 kg N/ha. Irrigation was applied with a rate of 20 mm per week during the warm season. To evaluate the effects on canopy structure we measured specific leaf weight (rag/cruZ), average leaf weight (rag), average twig height and average twig length. These variables were selected as they are the most likely to manifest changes over short time periods following changes in environmental conditions. The values of these parameters before initial treatments (autumn 1988) and after treatments (summer 1990) were analyzed. The results obtained show that water and nitrogen have a greater effect than phosphorus on tree canopy structure, at least during initial development.
Keywords: fertilization experiment; Irrigation experiment; leaves and twigs characteristics